MANAJEMEN KEPALA MADRASAH DALAM MENINGKATKAN KEPELATIHAN PUSTAKAWAN DI BIDANG TEKNOLOGI DAN INFORMASI - Ferdiansyah, M; Cahyani, Annisa Dwi; Aini, Syafira; Yusuf, Ja'far Maulana; Susanti, Try (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the management of madrasah principals in improving librarian training in the field of information technology. A qualitative approach with a case study design was employed, and data were collected through in-depth interviews with the madrasah principal and librarian. The findings reveal five key aspects: (1) the madrasah principal applies a participatory planning approach, though without a formal training needs analysis mechanism; (2) support is provided through technology infrastructure procurement and motivation, but facilities are not exclusively allocated for the library and no specific budget exists for librarian competency development; (3) training relies on online platforms and external activities with low frequency, with no internally organized training by the madrasah; (4) key constraints include disparities in human resource adaptation to new technologies, infrastructure limitations, and low training frequency that hinder the transfer of training; and (5) evaluation remains observational and based on physical indicators that do not directly reflect improvements in librarian technology competency, with no structured post-training follow-up mechanism. This study recommends adopting a comprehensive evaluation framework such as the CIPP model to build a complete competency development cycle, increasing the frequency of face-to-face training, encouraging librarian competency certification, allocating a dedicated budget for library human resource development, and improving technology facilities to ensure optimal and sustainable implementation of training outcomes.